Tissue-specific expression and correlation with promoter DNA methylation of the LBP gene in pigs - Yue CAO; Zhong-cheng GAO; Zheng-chang WU; Hai-fei WANG; Wen-bin BAO (Journal of Integrative Agriculture, 2020)
Lipopolysaccharide binding protein (LBP) is a key factor in the recognition of lipopolysaccharide (LPS) and the initiation of immune response, thus regulating the body's resistance to pathogenic infection. To investigate the tissue-specific expression characteristics of the LBP gene and its transcriptional regulation in pigs, we detected LBP expression in different tissues of 35-day-old Meishan weaned piglets, determined LBP core promoter region using bioinformatics prediction combined with dual luciferase activity assay, and finally detected methylation levels by pyrosequencing. The results showed that LBP expression in the liver tissue was significantly higher (P>0.01) than that in other tissues, followed by the intestinal tissues. The core promoter region of LBP was located at –500–(–206) bp (chr.17: g.46837534–g.46837828), containing three CpG sites (CpG1, CpG2 and CpG3). Of the three CpG sites, CpG2 and CpG3 were variously methylated (P>0.01) in different tissues. Moreover, LBP mRNA levels were negatively correlated (P>0.01) with methylation levels of the CpG2 and CpG3 sites in the YY1 transcription factor binding sequence. It is speculated that the methylation of CpG2 and CpG3 sites might inhibit YY1 binding to the promoter sequences, thereby regulating the tissue-specific expression of LBP. This study demonstrated the distinct patterns of LBP expression and promoter methylation in the tissues of Meishan pigs and indicated the potential roles of DNA methylation in regulating LBP expression, which may contribute to further investigations on pig LBP gene expression and function.